Clomiphene ovulation induction and higher‐order multiple pregnancy. (6th July 2013) - McDowell, Simon; Kroon, Ben; Yazdani, Anusch
Abstract : Clomiphene citrate is a widely used treatment for ovulatory dysfunction in women seeking pregnancy. The major adverse consequence of clomiphene use is the increased risk of multiple and higher‐order multiple pregnancy. Mechanisms for multiple pregnancy include dosing variation, adjuvant therapies, pretreatment weight loss and a cumulative effect of multiple clomiphene cycles. It has been suggested that the risk of higher‐order multiple pregnancy may be reduced with ultrasound monitoring, although there is limited evidence to support this practice.